True believer ebook - Sparks, Nicholas (Jeremy Marsh, 2005)
From New York Times bestselling author Nicholas Sparks, a supernatural love story between a journalist and a librarian who dare to believe in the impossible. Science journalist Jeremy Marsh specializes in debunking the supernatural–until he falls in love with the granddaughter of the town psychic, Lexie Darnell. When Jeremy receives a letter from Boone Creek, North Carolina, about ghostly lights appearing in a cemetery, he can't resist driving down to investigate. From the moment Jeremy sets eyes on Lexie, the town librarian, he is intrigued. And Lexie finds herself thinking of him more than she cares to admit.  Now, if they are to be together, Jeremy must do something he's never done before–take a giant leap of faith. True Believer will make you believe in the miracle of love.